SimplifyOkie dokie so first things first, you have to get rid of those parentheses! To do this you use the distributive property. -3(x+2) is the same thing as -3(x)+-3(2). that and you get -9=-3x-6. So you want to get x by itself to be able to find what x is, so you add 6 to both sides of the equation to get rid of the -6. So then you get -3=-3x. Then you must divide both sides by the coefficient of x, which would be -3. When you divide both sides by -3 you get -3/-3=x, which is the same thing as 1=x. Hope this helped!
So, if we look at the number pattern, we can see the numbers go up by 4.
The rule is Add 4.
So, to find the next two terms, we would add 4 to the last number shown, which is 15.
15 + 4 = 19
19 + 4 = 23
So, the next two terms are →19← and →23←.
Glad I could help, and good luck!
AnonymousGiantsFan
The answer to the question can be found by setting up a proportion such as 7/14.4=x/24.6 which gives you 11.9583 ft